(untitled) (Scientific journal of the Fergana State University, 2026)
Tomato fruit is a multicellular, multi-seeded, fleshy berry. The fruits vary in weight: from 20-50 g to 500-800 g. Those weighing up to 70 g are considered small, 70-100 g are medium, and those weighing more than 100 g are large. Tomato fruits are flat, flat-round, round, oval, pear-shaped, elongated-cylindrical, and others.